CD93 orchestrates the tumor microenvironment and predicts the molecular subtype and therapy response of bladder cancer. (August 2022) - Zheng, Xiaonan; Xu, Hang; Lin, Tianhai; Tan, Ping; Xiong, Qiao; Yi, Xianyanling; Qiu, Shi; Yang, Lu; Shen, Bairong; Ai, Jianzhong; Wei, Qiang
Abstract: Background: CD93 is newly reported to normalize vasculature and attenuate pancreatic cancer therapy response, but its role in bladder cancer (BLCA) is unknown. Method: The immunologic role of CD93 is analyzed across TCGA pan-cancers. The correlation between CD93 and BLCA clinical and tumor microenvironment features, predicted immunotherapy pathways, molecular subtypes, therapeutic signatures and mutation status was evaluated in TCGA-BLCA and other two BLCA cohorts. The impact of CD93 on immunotherapy response was validated by five real-world cohorts, and chemotherapy response was assessed with IC50. CD93-based risk model was constructed with LASSO regression and validated by seven independent cohorts. Result: CD93 is positively correlated with immunomodulators, tumor-infiltrating lymphocytes (TILs) and immune checkpoints across pan-cancers. In BLCA, CD93 leads to higher T cell inflamed score and expression of immune checkpoints. However, CD93 is indicative of more aggressive clinical features, worse survival, more tumor-associated macrophages and regulatory T cells recruitment, less recognition and killing of cancer cells by T cells, lower predicted chemotherapy and immunotherapy response, which is further validated by immunotherapy cohorts (IMvigor210: 16.11% vs 29.53%; GSE176307: 15.56% vs 20.93%). Notably, CD93 correlates with enriched neuroendocrine subtype and epithelial-mesenchymal transition differentiation, while CD93-low group has enriched luminal subtype. Pathways including hypoxia and Wnt-β-catenin are enriched along with CD93 expression, and more frequent FGFR3 mutation is also observed. Lastly, the CD93-based risk model, validated by seven independent cohorts, is powerful in distinguishing the survival probability of BLCA (3-year AUC 0.808). Conclusion: CD93 plays a critical role in tumor immune regulation. CD93 expression indicates more aggressive clinicopathological status and molecular subtypes of BLCA and worse therapy response, which implies that combing anti-CD93 therapy with immunotherapy (or chemotherapy) may be potentially beneficial for BLCA in clinical practice. Highlights: In BLCA, CD93 is indicative of more aggressive clinical features, worse survival, less recognition and killing of cancer cells by T cells, molecular subtypes, lower chemotherapy response and lower immunotherapy response, which is further validated by five immunotherapy cohorts (two BLCA, one renal cell carcinoma and two melanoma). Combing anti-CD93 therapy with immunotherapy (or chemotherapy) may be feasible and beneficial for BLCA clinical practice.